Alternatif Penghukuman Selain Penjara: Analisis Hermeneutika Kritis Dan Critical Legal Studies - Murdoko; Mohammad Syifa Amin Widigdo (Fakultas Hukum Universitas Islam Indonesia, 2023)
The prison model as a form of punishment and retribution for acts and perpetrators of crimes has received criticism from some scientists and legal activists. Critical Legal Studies (CLS) personnel criticize the model of punishment by imprisonment because of its positivistic nature. The norm of applying prison law is considered universal without regard to the relativity and particularity of facts which cannot be separated from various social contexts. For this reason, this research examines and considers alternative models of punishment outside prison institutions that accommodate the particularity of facts and cases in order to obtain a model of punishment that is not only retaliatory for the perpetrators of crimes, but also educational in nature while respecting their right to freedom. By using a critical hermeneutic approach combined with CLS, this study concludes that supervision as punishment can be applied as an alternative model of punishment beyond imprisonment that is deemed to be more humane and effective.Key Words: Hermeneutics; prison; supervision; critical legal studies; punishment. AbstrakModel penjara sebagai bentuk hukuman dan pembalasan untuk tindak dan pelaku kejahatan mendapat kritik dari sebagian ilmuwan dan aktivis hukum. Kalangan CLS (Critical Legal Studies) mengkritik model penghukuman dengan penjara karena wataknya yang positivistik. Norma penerapan hukum penjara dianggap universal tanpa mengindahkan relativitas dan partikularitas fakta yang tidak bisa dilepaskan dari konteks sosial yang beragam. Untuk itu, penelitian ini mengkaji dan menimbang model alternatif penghukuman di luar institusi penjara yang mengakomodasi partikularitas fakta dan kasus agar mendapatkan model penghukuman yang tidak hanya bersifat pembalasan terhadap pelaku kejahatan, namun juga bersifat pendidikan dengan tetap menghargai hak kemerdekaannya. Dengan menggunakan pendekatan hermeneutika kritis yang dikombinasikan dengan CLS, kajian ini menyimpulkan bahwa pengawasan sebagai hukuman dapat diterapkan sebagai alternatif model penghukuman di luar penjara yang lebih humanis dan efektif.Kata-kata Kunci: Hermeneutika; penjara; pengawasan; critical legal studies; hukuman